(3eaGgje MOjKI aj GdJShjb GdHfcjs - (3eMehO jhSa(B, (3Ybdgs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2009)
(3ebOeI aj GdJQhjL GdJLGQj ,h WHjYI GdfTGW GdJShjbj , GdJQhjL cYedjI GJUGd , Gdeaghe GdMOjK dGOGQI GdJShjb , GdJShjb GdaYGd ,GOGQI GdJShjb h GdGWGQ GdfXQj (B.s
(3eQGLY U(B.211s
Keywords: (3GdHfhcs; (3GdJShjbs; (3JQhjL GdJLGQIs